Performance comparison of chlorinated chiral stationary phases in supercritical fluid chromatography for separation of selected pyrrolidone derivatives - Anca-Elena Dascalu; Alina Ghinet; Muriel Billamboz; Emmanuelle Lipka (Elsevier, 2019)
The effects of two chlorinated chiral stationary phases, namely, Lux Cellulose-2 and Lux i-Cellulose-5, flow-rate, percentage of co-solvent and chemical structures of the compounds on retention and resolution were studied within this article. In this work a backpressure of 150 bar, a temperature of 40 °C and 10% of methanol as co-solvent were chosen as operating conditions. The optimum flow-rate was 2 mL/min. The percentage of co-solvent was studied between 7.5% and 15%. We have observed that 15% of methanol gave the best results for most of the compounds. For all the derivatives, the Lux Cellulose-2 provided better resolutions going from 1.50 to 3.59 compared with Lux i-Cellulose-5. Keywords: Antibacterial compounds, Chirality, Enantiomers, Flow-rate, Particle size